PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - D. Muhamad Yamin; Rika; Dede Suharna (Universitas La Tansa Mashiro, 2025)
Banking sector companies are an important part of the Indonesian economy, having their own appeal as reflected by the company's financial performance in investment activities for their shares in the capital market. The company value proxied by Price to Book Value (PBV) shows how far a company is able to create company value relative to the amount of capital invested. This study was conducted to determine the effect of leverage and company size on company value in banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The method used a quantitative method, the population used 47 banking companies, using a purposive sampling technique, 37 banking companies are the samples in this study. Data collection by accessing leverage data (DER), company size (SIZE) and company value (PBV) in each company obtained from the site www.idx.co.id. The data analysis technique used multiple linear regression analysis using the SPSS 20 program. Research results: partially leverage has a negative effect on company value, while company size has a positive and significant effect on company value. Meanwhile, simultaneously the leverage and company size variables have a positive and significant effect on company value in banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period.